(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: Inhaled corticosteroids are crucial in managing childhood asthma, reducing inflammation, and preventing exacerbations. However, parental ICS phobia, fueled by growth concerns, weakens immunity, and dependency fears hinder adherence and asthma control. This study aims to gauge ICS phobia prevalence among parents of asthmatic children and pinpoint related factors. Methodology: This study conducted at CMH, Muzaffarabad from June to November 2024 included 168 parents of children aged 2–10 years with asthma using ICS therapy. Information on demographics, ICS adherence, parental concerns, and asthma control was collected through a structured questionnaire. ICS phobia was identified based on misconceptions, adherence, and alternative treatment preferences. Data were analyzed using SPSS version 26, with statistical significance at p<0.05. Results: Among parents, ICS phobia prevalence was 50.6%, slightly higher in females (53.8%) than males (45.5%) (p=0.283). The highest phobia rate was seen in parents with higher secondary education (69.6%) and lowest in those with undergraduate education (35.0%) (p=0.130). Urban dwellers had a higher ICS phobia rate (54.9%) than rural residents (44.2%) (p=0.166). The main concerns were social media misconceptions (41.1%) and fear of inhaler dependence (27.9%). Conclusion: Parental ICS phobia in asthmatic children is common due to misinformation, rather than demographics. This fear affects treatment adherence and asthma control. Targeted education and counseling by healthcare providers are essential to address concerns and enhance pediatric asthma outcomes.